Analisis Peran Strategis Konsultan Pajak X didalam Meningkatkan Efisiensi Pengelolaan Pajak dan Kepatuhan Pajak - Joannita Btari Kinnasih; Diah Anugrah Sharasanti (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to analyze the strategic role of Tax Consultant X in Surabaya in improving the efficiency of tax management and tax compliance for its clients. The motivation for this study stems from the increasing complexity of tax regulations, which makes it difficult for taxpayers to understand and fulfill their tax obligations appropriately, making the decision to use a tax consultant increasingly relevant. The research method used is quantitative and descriptive, based on a survey of 43 respondents who are clients of Tax Consultant X. Data were collected using a Likert-scale questionnaire and analyzed to describe client perceptions of the effectiveness of Tax Consultant X's services. As many as 93% of respondents reported that the consultant was very helpful in tax calculations, 91% considered the consultant effective in solving tax problems, and 91% reported that the consultant helped with timely tax reporting. In addition, 75% of respondents reported an increase in tax compliance after using the consultant's services, while 88% considered the consultant to play a role in improving the efficiency of tax management. Client satisfaction and loyalty were also high, indicated by 91% of respondents who intended to use the consultant's services in the future.